ax squared - 18ax + 77a``

factor completely

### 2 Answers | Add Yours

Factor completely:

`ax^2-18ax+77a` Take out the common factor a:

`= a(x^2-18ax+77a)`

Now factorize the brackets using the factors of `x^2 ...(x times x)` and the factors of 77 (in this case `11 times 7) ` to render a middle term of 18:

`therefore = a(x-11)(x-7)`

**Ans: = a(x-11)(x-7)**

**Sources:**

`ax^2-18ax+77a=a(x^2-18x+77)=`

`=a(x^2-11x-7x+77)=a[x(x-11)-7(x-11)]=`

`=a(x-11)(x-7)`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes